Transformation of Legal Objects in the Digital Age: Challenges and Opportunities - Numan, Muhammad; Wilda Rahmawati, Alfi; Faisol, Muhammad; Mustika, Dian; Mulyani, Mulyani (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
The legal object is an essential component in the modern legal system, serving as the subject of legal relations between the parties involved. Traditionally, legal objects include transferable objects and rights that fulfill the rights of legal subjects. This research uses qualitative methods, mainly through literature review, by analyzing various primary legal sources such as laws and official documents, in addition to secondary sources such as scientific journals and relevant articles. Qualitative data analysis aims to explore the evolving paradigm of legal objects, their practical applications, and the resulting legal implications. The findings show that the concept of legal objects has expanded significantly in response to social, economic, and technological changes. In today's digital age, intangible assets such as intellectual property rights, personal data, and cryptocurrencies have gained prominence, thus requiring corresponding legal recognition. This evolution presents new challenges to the legal system, prompting the need for responsive and adaptive policy development. For example, Indonesia's Personal Data Protection Law establishes a legal framework for managing and protecting personal data as a new legal object, reflecting the need for contemporary legal adaptation.